Engineering Improved Photosynthesis in the Era of Synthetic Biology - Batista-Silva, Willian (Plant Commun, 2020)
Much attention has been given to the enhancement of photosynthesis as a strategy for the optimization of crop productivity. As traditional plant breeding is most likely reaching a plateau, there is a timely need to accelerate improvements in photosynthetic efficiency by means of novel tools and biotechnological solutions. The emerging field of synthetic biology offers the potential for building completely novel pathways in predictable directions and, thus, addresses the global requirements for higher yields expected to occur in the 21st century. Here, we discuss recent advances and current challenges of engineering improved photosynthesis in the era of synthetic biology toward optimized utilization of solar energy and carbon sources to optimize the production of food, fiber, and fuel.